Rekomendasi Perbaikan Proses Bisnis Dengan Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus: Badan Penjaminan Mutu, Universitas Widyagama Malang) - Dinda Agnes Putri; Nanang Yudi Setiawan; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Badan Penjaminan Mutu is the division which play an important role in maintaining the quality of all aspects in Widyagama University in Malang. In the process to business function of control, monitoring, and quality evaluation, and performance of personnel, found some potential problems to achieve the vision and mission of Badan Penjaminan Mutu. The problems are manual business processes, inefficient and not integrated system, complex activities, and inefficient storage system. Therefore, analysis and evaluation also improvement of business process is needed to solve the problems and to maximize the existing process. This research uses Business Process Modelling and Notation (BPMN) to make business process diagrams, the Failure Mode and Effect Analysis (FMEA) method to evaluate and analyse business processes, and Business Process Improvement (BPI) method to make improvements. Afterwards, simulation of current business processes (as is) and recommendations (to be) were implemented to validate and demonstrate the effectiveness of the recommended business process. In the simulation process, the evaluation of business process is valid, and the time analysis is incresed by 61.13%. This happens because manual activities are replaced by system.